2020
DOI: 10.1186/s43055-020-0148-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of gastric cancer by MDCT gastrography: diagnostic characteristics and management potential

Abstract: Background: Gastric cancer is regarded as the fifth most frequent tumor globally but the third most common fatal illness. As early as possible, we diagnose cancer stomach especially at early stages, the higher the rate of life. Nevertheless, most cases are diagnosed at late cases where surgery is not of the same benefit at early stages because of clinically indefinite symptoms. The prospective study goal is to estimate the role of MDCT in diagnosis and staging of cancer stomach. Results: In our study, it was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Yogaraj et al (20) found that Multi-detector CT was an effective imaging method for the stomach based on the correlation between histology results and CT diagnosis. Zytoon et al (21) found that CT was found to be specific and accurate in the detection of all stages of gastric cancer, with specificity ranging from 93-97% and accuracy ranging from 9-92.5%. This suggests a strong correlation between the two methods of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Yogaraj et al (20) found that Multi-detector CT was an effective imaging method for the stomach based on the correlation between histology results and CT diagnosis. Zytoon et al (21) found that CT was found to be specific and accurate in the detection of all stages of gastric cancer, with specificity ranging from 93-97% and accuracy ranging from 9-92.5%. This suggests a strong correlation between the two methods of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of MDCT in detecting distant metastasis of gastric cancer is as high as 94.5%, but the sensitivity to gastric cancer peritoneal metastasis is of relatively low value. Of note, a study which is published in 2020 found that multiplanar reformations (MPR) and volume rendering (VR) of MDCT provide more accuracy than MDCT axial images in diagnosing all stages of gastric cancer [92.5 vs. 80%; P =0.0009; ( 61 )].…”
Section: Staging Of Advanced Gastric Cancermentioning
confidence: 99%